Pengaruh Dukungan Sosial Keluarga, Efikasi Diri dan Kecerdasan Spiritual terhadap Kecemasan Mahasiswa Semester VIII IAKN Manado - Sri Vani Melati Lahimade; Benny B. Binilang; Olivia C. Wuwung (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to find out the direct and indirect influence between family social support on student anxiety, self-efficacy of student anxiety, family social support for spiritual intelligence, self-efficacy of spiritual intelligence, spiritual intelligence on student anxiety, family social support for student anxiety through intelligence spiritual, self-efficacy against anxiety through spiritual intelligence at the Manado State Christian Institute. To achieve the research objectives, the researchers used a quantitative. Based on the results of the study, the researcher concluded that (1) Family Social Support has a direct effect on student anxiety (2) Self-efficacy has a direct effect on student anxiety (3) Family social support has no direct effect on spiritual intelligence (4) Self-efficacy of spiritual intelligence has a direct influence (5) spiritual intelligence against anxiety has a direct influence on student anxiety (6) Family social support has no influence on student anxiety through spiritual intelligence (7) self-efficacy has an influence on student anxiety through spiritual intelligence